2012
DOI: 10.1364/ol.37.003984
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Yb:CaGdAlO_4 thin-disk oscillator

Abstract: A mode-locked thin-disk laser based on Yb:CALGO is demonstrated for the first time. At an average output power of 28 W we obtained pulses with a duration of 300 fs and a pulse energy of 1.3 μJ. 197 fs pulses with 0.9 μJ of energy were achieved at an average output power of 20 W. The shortest pulse duration measured in our experiments was 135 fs with a spectrum centered at 1043 nm. The experiments also revealed a very broad tunability from 1032 to 1046 nm with sub-200 fs pulses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 15 publications
0
56
0
Order By: Relevance
“…The first modelocking experiments using the promising material Yb:CALGO (Yb:CaGdAlO 4 ) [86,87] in the thin-disk configuration were recently reported [69,88]. This material combines a very broad and smooth emission bandwidth with a thermal conductivity comparable to Yb:YAG (6.5 W·m for 2% doping).…”
Section: State-of-the Art and Recent Experimental Resultsmentioning
confidence: 99%
“…The first modelocking experiments using the promising material Yb:CALGO (Yb:CaGdAlO 4 ) [86,87] in the thin-disk configuration were recently reported [69,88]. This material combines a very broad and smooth emission bandwidth with a thermal conductivity comparable to Yb:YAG (6.5 W·m for 2% doping).…”
Section: State-of-the Art and Recent Experimental Resultsmentioning
confidence: 99%
“…The interest to Yb:CALGO is motivated by its beneficial spectroscopic and thermal properties [2,3], that allowed for realization of high-efficient and high-power bulk [4,5] and thin-disk lasers [6,7], as well as generation and amplification of ultrashort pulses [8][9][10][11][12][13][14] with pulse production as short as 32 fs [10]. However, Yb:CALGO demonstrate very particular thermal properties involving a strong anisotropy of its lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been observed that pumping above 100 W may involves strong thermal beam deformation, both in thin-disk or bulk configuration. On the first hand, in thin disk configuration [11], a thermal astigmatism has been identified as a limitation for high power production. On the second hand, in bulk configuration this time, it was recently demonstrated that Yb:CALGO can provide unique stabilization of laser mode at high pump powers [15], the effect that cannot be completely understood on the basis of reported properties up to now.…”
Section: Introductionmentioning
confidence: 99%
“…The emission spectrum is broadband and lasing was demonstrated between 1018nm and 1052nm [2]. High power with good beam quality, as well as 192fs short pulses and 1.3µJ energy, were obtained from a thin-disk oscillator [3], and 12.5W with sub-100fs pulses have been extracted out of a single-crystal cavity at 80MHz repetition rate [4].We report here what is, to our knowledge, the highest power generated by a bulk Yb:CaAlGdO4 oscillator, to be later used for a regenerative amplifier aiming at the multi-mJ level. To overcome the thermal effects in a single crystal, the thermal load is distributed between two shorter crystals in a symmetric resonator, as demonstrated in [5].…”
mentioning
confidence: 99%
“…The emission spectrum is broadband and lasing was demonstrated between 1018nm and 1052nm [2]. High power with good beam quality, as well as 192fs short pulses and 1.3µJ energy, were obtained from a thin-disk oscillator [3], and 12.5W with sub-100fs pulses have been extracted out of a single-crystal cavity at 80MHz repetition rate [4].…”
mentioning
confidence: 99%